Improving the performance of inverted polymer solar cells through modification of compact TiO2 layer by different boronic acid functionalized self-assembled monolayers - Kirbiyik, Cisem; Kara, Duygu Akin; Kara, Koray; Buyukcelebie, Sumeyra; Yigit, Mesude Zeliha; Can, Mustafa; Kus, Mahmut (Elsevier Science Bv, 2019)
In this study, we demonstrate the use of a series of boronic acid functionalized self-assembled monolayers (SAMs) to improve photovoltaic device performance P3HT and PCBM based solar cells. The SAMs treated compact TiO2 (c-TiO2) layer was utilized as an electron transport layer for inverted polymer solar cells (PSCs) with a configuration of FTO/c-TiO2/SAM/P3HT:PCBM/PEDOT:PSS/Ag. The modified with 3,4,5-methoxyphenylboronic acid (3-OMe) SAM shows the best improving due to the enhancement of J(sc) and V-oc. in device, which leads to a 26% improvement (2.8%) over non-modified device (2.2%). The enhancement in the modified devices is achieved by SAM modification reducing recombination of charges and improving charge selectivity. These results prove that the surface and electrical properties of compact TiO2 (c-TiO2) layer can be easily tuned as well as the upper layer morphology can be controlled by SAM modification.
Keywords: Self-assembled monolayer; Bulk heterojunction; Polymer solar cells; Compact TiO2